FOODS INGREDIENTS MANAGEMENT: INBOUND AND OUTBOUND HALAL MANAGEMENT BEST PRACTICE (Journal of Technology and Operations Management, 2018)
Foods and ingredients management in the inbound and outbound of warehouse has become significant priority to ensure the quality of halal products. This study will benefit the society among the Muslims and Non-Muslims communities. Manufacturers can interconnect the information to improve and identify factors affecting the consumers who are doubtful of choosing halal products. The objective of the study focus to examine the inbound and outbound efficiency of food ingredients management for halal management best practice in the warehouse. The researchers chose Saudi Cold Storage Sdn. Bhd as the model and respondents of the study. Questionnaires consisted of 26 questions are applied and distributed to the company’s employees. Inbound and outbound efficiency of food ingredients management are the independent variables for halal management best practice who acted as dependent variable. Theoretically, this research contributed the study on the inbound and outbound efficiencies of food ingredients management affected the halal management best practice. Practically, the study is applicable for managers in the halal food industries in their operational decisions making. The outcome of this research is positively reacted and explored for future studies related to halal warehousing and its operations.